Philometra cephalus (Nematoda) infection in the gonads of the long-arm mullet Valamugil cunnesius : host-parasite relation - Radhakrishnan, S; Magitha, Beevi; Deepthi, G R; Treesa, Radhakrishnan (Indian Journal of Fisheries, 2016)
The long-arm mullet, Valamugil cunnesius (Val.) harbours an infection in their gonads, by the dracunculid nematode, Philometracephalus Ramachandran. Though P. cephalus was reported from Mugil cephalus way back in 1975 and the parasite wasreported to cause serious harm to the gonads of its host, so far no attempt has been made to study its nature of infection. Thispaper reports the results of the study on the host-parasite relation of P. cephalus. P. cephalus is highly host-specific and itinfects both testis and ovary of V. cunnesius. The prevalence of infection was 41.7%; it was much higher in females (48.3%)than in males (28.2%). Prevalence registered an increasing trend with length of fish and advancing gonad maturity. Thoughhepato-somatic index, gonado-somatic index and condition factor were adversely affected by the infection, the greatestimpact of the infection was on the fecundity, which was significantly lowered, by nearly four times, in the infected fish(mean fecundity = 13.8 x 103) compared to the uninfected fish (mean fecundity = 52.1 x 103). The high prevalence ofthe infection in females and the significant reduction in fecundity together could have serious adverse effects on the hostpopulation.